Sustainable Production of Insecticidal Compounds from Persea Indica - Zuniga-Navarro, G; Contreras-Arredondo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In this work, we have investigated the accumulation of ryanoids in different plant parts (leaves, stems and roots) of aeroponically grown Persea indica cloned trees (one-year-old cloned individuals) and a selected mature, wild tree. We tested the insect antifeedant (against Spodoptera littoralis, Myzus persicae and Rhopalosiphum padi) and nematicidal (against Meloidogyne javanica) effects of ethanolic extracts from these different plant parts. The HPLC-MS analysis of P. indica extracts showed that mature tree (wild) leaves had two times more chemical diversity than stems. Aeroponic plants showed fewer differences in chemical diversity between leaves and stems, with the lowest diversity found in the roots. Ryanodane epiryanodol (1) was present in all the plant parts, with the mature stems (wild) containing the highest amount. The aeroponic stems also accumulated ryanoids including 1, cinnzeylanol (2) and cinnzeylanone (4). The insect Spodoptera littoralis was strongly affected by the stem extracts, while leaf extracts were moderately active. Based on predicted vs. real antifeedant values, we concluded that the ryanoid content (1 or a combination of 2, 4 and 1) explained the antifeedant effects of the stem extracts, while additional components contributed to the activity of the leaf extracts. Therefore, careful individual selection of P. indica seedlings should be carried out prior to proceeding with aeroponic cultivation in order to obtain ryanodane-rich stem or leaf extracts with strong antifeedant effects on S. littoralis. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.